ANALISIS TINGKAT VOLUME OKSIGEN (VO²MAX) PESERTA DIDIK MENGIKUTI EKSTRAKURIKULER SMP NEGERI 1 MARTAPURA - Muhamad Salehen; Ramadhan Arifin; Lazuardy Akbar Fauzan (JURNAL ILMIAH PENJAS (Penelitian, Pendidikan dan Pengajaran), 2024)
Observations made on students at SMP Negeri 1 Martapura who took part in extracurricular activities were that many students got tired easily both when doing PJOK lessons, general learning, and during futsal practice and futsal matches. This can be influenced by the level of oxygen volume (VO2Max) possessed by each student. This research aims to find out how much oxygen volume level (VO2Max) is possessed by students who take part in extracurricular activities at SMP Negeri 1 Martapura. With only one variable, this research is a quantitative descriptive research. The sample consisted of twenty students from SMP Negeri 1 Martapura who had completed the Multistage Fitness Test (MFT). The MFT calculation form is used in the data collection process to ensure the level and feedback of each student, after which the VO2Max level is calculated. Based on the research results, students at SMP Negeri 1 Martapura have VO2Max levels which are divided into four categories, namely good (5%), moderate (50%) and very bad (25%) with an average VO2Max value of 38.035.